Dinâmicas do pentecostalismo evangélico no estado de Rondônia: um estudo de sociologia da religião - Maia, César Portantiolo (2022)
Sociology of religion has long been concerned with studying the relationships established between religions and state power, investigating the degree of distance or proximity between such institutions. In our research, we are concerned with analyzing how this relationship has been established in recent years in which political polarization has consolidated an extreme right-wing in Brazil. Marked by aspects such as the defense of a conservative morality, economic liberalism, and radical positions regarding quite controversial issues such as gun ownership, reduction of the age of criminal responsibility, anti-abortion, pro-traditional family, anti-feminist, and anti-LGBTQA+ discourse, such groups have gained relevance in the Brazilian social scene. Most of the time, these positions are based on God and the patriarchal social structure. The election of Jair Bolsonaro, sustained with strong evangelical support, sets a precedent for thinking that Pentecostalism would be the basis for sustaining the ideas of the Brazilian far-right. This was the initial hypothesis of this research, which triggered a study on religion and politics in the region with the highest proportion of Pentecostals in Brazil. Rondônia, one of the youngest states in the federation, formed by the miscegenation of Brazilians coming from various regions of the country, is the place with the most Pentecostal population in Brazil, according to data from the 2010 census of the Brazilian Institute of Geography and Statistics (IBGE). The religious option is also reflected in the political option, as the governor and the most voted senator in the 2018 elections are avowedly Pentecostal. In addition, 5 of the 8 federal deputies express close relations with conservative Christian precepts. However, there is no adherence to all the ideas of the extreme right by these political leaderships. Making use of methodologies that mix quantitative and qualitative data analysis, we used data produced by IBGE and information collected in the field through questionnaires applied to Pentecostals. We also carried out an analysis of the social networks of political leaders and interviews with social and religious leaders, through which we demonstrated the socio-political articulations around common themes such as economic, moral, and religious agendas. Thus, we analyze the paths taken by Pentecostalism in its expansion and performance in the spaces of power in the State of Rondônia. This thesis defends the idea that the Pentecostal precepts are not the same as those defended by the extreme right; there are convergent points, but there are also divergences. The distancing from the ideas defended by the left on issues such as abortion, weapons, feminism, and defense of the LGBTQA+ cause, led to a rapprochement with the extreme right, in addition to the opportunity to ascend to federal power. However, because there is no common ground, it is possible that in the near horizon there will be dissociation of this link between Pentecostals and far-right politics.